Mobilizing or Chasing Voters on Facebook? Analysing Echo-Chamber Effects at the UK Parliamentary General Election 2019. Issue 1 (19th July 2021) - Power, Sam; Mason, Ben
Abstract: Alongside the growth of online campaigning has been an increased anxiety around its effects on democratic institutions and processes. Many have suggested that in a (new) media environment that privileges choice, citizens will increasingly segment themselves into echo chambers, tuning out dissenting voices. But the debate on the existence of echo chambers is mixed, and the extent to which political parties campaign to easily persuadable (and pre-disposed) electorates is unclear. In this article, we present a case study of the Facebook campaign activity of the Conservatives, Labour and the Liberal Democrats at the UK's parliamentary general election in 2019. Utilising an analysis of the Facebook Ad Archive's Graph Application Programming Interface (API), we find that political parties do not consistently campaign to their easily persuadable electorates—often chasing votes as much as they mobilise supporters. The evidence that parties campaign to specific echo chambers online is therefore, at best, mixed.